Sexual Potency Before and After Radical Prostatectomy - Finkle, Alex L. (1985)
A triad of factors can favorably influence the maintenance of sexual potency after radical prostatectomy: the surgical avoidance of cavernous neurovascular bundles, the preoperative interest of the surgeon in broaching the subject with the patient and the continued encouragement given the patient by his attending physician as to probable preservation of sexual competency following the surgical procedure.